Ampullae infection of the malpighian tubules of bombyx mori by alphabaculovirus - Santorum, Marilucia; Beu, Célia Cristina Leme; Ribeiro, Lucinéia de Fátima Chasko; dos Santos, Juliana Souza; dos Santos, Daniela Carvalho [UNESP]; Brancalhão, Rose Meire Costa (Univ Federal Uberlandia, 2017)
Alphabaculovirus is a genus of the entomopathogenic virus, whose species Bombyx mori nucleopolyhedrovirus (BmNPV) infects the silkworm, Bombyx mori, which is an important insect in the sericulture industry. A geographic isolate of BmNPV was identified in the state of Parana, Brazil. It was infecting B. mori larvae and various organs and target tissues were identified, however, there was no information about the infection of Malpighian tubules (MT). The MT comprises the excretory system of B. mori and acts in the elimination of toxic substances and in hydroelectrolytic homeostasis. Thus, the present study examined the susceptibility and cytopathology of B. mori MT to BmNPV. To this end, hybrid fifth instar larvae were inoculated with a virus suspension at different days post-inoculation (dpi). MT segments were collected and divided into the ampullae, proximal, medial and distal regions. These were processed for light microscopy and transmission electron analysis. The MT regions revealed differences in susceptibility to BmNPV and the ampullae in its transition area was infected from the sixth dpi; the other regions did not reveal any evidence of infection. The transition area of the ampullae has not been previously described in Lepidoptera and its cytopathology revealed a hypertrophic nucleus with viroplasm, followed by the formation and development of viral polyhedra, which are common characteristics of infections by Alphabaculovirus. Thus, infection of the ampullae of the MT of B. mori by BmNPV, together with other known targets, compromises the metabolic balance of the insect, which results in consequences for silk production and damage to the sericulture sector.
Infecção de células da ampola dos túbulos de malpighi de bombyx mori pelo alphabaculovirus
Keywords: Baculovirus; Bombyx mori; Silkworm; Cytopathology; Lepidoptera; Excretory system